Photogrammetric image analysis ISPRS conference, PIA 2011, Munich, Germany, October 5-7, 2011: proceedings - Stilla, Uwe (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the ISPRS Conference on Photogrammetric Image Analysis, held in Munich, Germany, in October 2011. The 25 revised full papers presented were carefully reviewed and selected from 54 submissions. The papers are organized in topical sections on orientation, matching, object detection, 3D reconstruction and DEM, classification, people and tracking, as well as image processing.